Emerging roles of microRNAs in the metabolic control of immune cells. (1st October 2018) - Yao, Qiuming; Song, Zhenyu; Wang, Bin; Zhang, Jin-an
Abstract: Immunometabolism is an emerging field that focuses on the role of cellular metabolism in the regulation of immune cells. Recent studies have revealed an intensive link between the metabolic state and the functions of immune cells. MicroRNAs (miRNAs) are small non-coding, single-stranded RNAs generally consisting of 18–25 nucleotides that exert crucial roles in regulating gene expression at the posttranscriptional level. Although the role of miRNAs in immune regulation has long been recognized, their roles in immunometabolism have not yet been well established. Over the past decade, increasing studies have proven that miRNAs are intensively involved in the metabolic control of immune cells including macrophages, T cells, B cells and dendritic cells. In this review, we highlight recent emerging findings in the miRNA-mediated metabolic control of immune cells. Highlights: Many miRNAs can regulate the metabolism of immune cells including macrophages, T cells, B cells and dendriic cells. This review highlights recent emerging findings in the miRNAs-mediated metabolic control of immune cells. This review provides a better understanding of the miRNAs-mediated metabolic reprogramming of immune cells.